Functional Behaviour of Materials, Introduction to Semiconductors - Knowles K.M; Dunleavy Chris; DoITPoMS, University of Cambridge
Este conjunto de animaciones cubre los principios y las aplicaciones de los semiconductores. Abarca los siguientes elementos:Schottky barrier contact for a metal and a n-type semiconductorRectifying contact for a metal and a p-type semiconductorMetal<U+0096>semiconductor junction: Ohmic contactRectifying contact at p-n semiconductor junctionThe bipolar transistorThe metal oxide semiconductor field effect transistor (MOSFET)